The sons of Katie Elder - Hathaway, Henry, 1898-1985.; Wright, William H., 1902-1980.; Weiss, Allen; Essex, Harry J., 1910-1997.; Jennings, Talbot; Wayne, John, 1907-1979.; Martin, Dean, 1917-1995.; Hyer, Martha; Anderson, Michael, 1943 August 6-; Holliman, Earl, 1928-; Slate, Jeremy; Gregory, James, 1911-2002.; et al. (Hollywood, California Paramount Home Video, 2001)
The day that Katie Elder is buried, her four sons return home to Clearwater, Texas, to pay their last respects. It is a he-man story, as well as, a drama of the maternal influence of Katie Elder, her sacrifice, love and incredible valor. The hopes and aspirations for her sons is movingly communicated from beginning to conclusion.
Originally produced as a motion picture in 1965.
Based upon a story by Talbot Jennings.
Special features: Interactive menus, scene selection, theatrical trailer.
Music by Elmer Bernstein.
John Wayne, Dean Martin, Martha Hyer, Michael Anderson, Jr., Earl Holliman, Jeremy Slate, James Gregory, Paul Fix, George Kennedy, Dennis Hopper.
DVD, widescreen presentation, enhanced for 16:9 TVs; Dolby Digital mono.
Keywords: Jennings, Talbot -- Film adaptations; Mothers and sons -- Drama; Women pioneers -- West (U.S.); Frontier and pioneer life -- West (U.S.) -- Drama; Brothers -- Fiction; Video recordings for the hearing impaired; Women pioneers; Mother-son relationship -- Fiction; Closed caption video recordings; West United States; Videodiscs; Video recordings for the hearing impaired (M-N); Film adaptations; Drama; Feature films; Video recordings for the hearing impaired; Western films